Cultural Image of the Jewish in Lithuania and Nationalists Ideology - Ivanovas, Bernaras (Problemos, 2002)
In the beginning of the 4th decade (XX c.) in Lithuania we can see positive image on the cultural level of Lithuanian Jews in the Nationalists party's press. First of all, the aspects of this image were closely connected with ethno-nationalism and idea of cultural loyalty to Lithuanian nation, that was master of the national state. The Nationalist party at the same tries to assure the unity of Jewish community and preferred Zionist group, which main goal was to immigrate to Palestine. This group concentrates almost all positive characteristics of the positive image of Lithuanian Jews. That proves that loyal Jew for Lithuanian Nationalists party was just Zionist, the Jew who wants to leave that country. Another group, that had positive image was group of religious orthodoxies. Nationalists preferred them, because they didn't want to integrate to Lithuanian society. At the end of the 4th decade the attitude toward Jews had changed. First of all Nationalist's propaganda concentrated on the group of liberal Jews and on the usage of Russian language in Jewish community, but on another hand the image of Jewish communist was not very popular. Generally, all negative features were attributed to the Jews, who wanted to integrate to Lithuanian society and who wanted to take positions, that, according to the ideology of nationalists, were attributed just for Lithuanians. At the end we can say that motivation of cultural Jewish image was based on the principals of Nationalist's ideology which main goal was to create house only for Lithuanian nation. Other national minorities, according Nationalists leader and Lithuanian prcsident A. Smetona, had only one possibility: to leave or to help for Lithuanians in creating their national house.
Keywords: Jew; nationalísm; Nationalist party; cultural loyalty